Cognitive niche - Đorđe Petronić; Igor Vujović (Биомедицинска истраживања, 2020)
In a joint publication with Alfred Russell Wallace, Charles Darwin presented the theory which stated that all life forms were developed by natural selection in which the fight for survival had the effect similar to artificial intelligence applied to selective breeding. Despite a coincidence of views concerning the origin of life, these two scientists had their disagreements. Wallace argued that intelligence could have never arisen through the process of natural adaptation, but rather as a consequence of intelligent design. On the other hand, Darwin insisted that human intelligence could only be explained by the theory of evolution. This difference in point of views on the matter is a manifestation of the difference in the efforts to answer the question: "Why are people so intelligent?" In this context, the main aim of the study is to present a literature Reviews concerning evolutionary psychology and to provide an explanation of the evolution of human intelligence. In other words, the study seeks to explain why people are able to accomplish such intellectual exploits as the ones found in mathematics, science, philosophy, law, etc., bearing in mind that such abilities or talents cannot be found in the original human habitat. The results have showed that evolutionary psychologists consider humans to be so intelligent due to the fact that they have evolved to fill the "cognitive niche". The cognitive niche is a survival mode characterized by managing the environment through mediating cognition and social cooperation.
Keywords: intelligence; cognitive niche; evolution; adaptation